2019
DOI: 10.1016/j.scitotenv.2019.03.489
|View full text |Cite
|
Sign up to set email alerts
|

Use of passive sampling and high resolution mass spectrometry using a suspect screening approach to characterise emerging pollutants in contaminated groundwater and runoff

Abstract: Highlights • Design of a novel Empore™ disk-based passive sampler to enable the deployment in well bore holes for groundwater monitoring. • Novel passive sampler used to monitor groundwater and stormwater runoff from infiltration systems. • Combination of passive sampling and liquid chromatography/high resolution mass spectrometry for groundwater and stormwater runoff screening. • Development of an analytical procedure based on a suspect screening workflow providing a rapid and comprehensive analysis. • Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Due to their ability to retain a large range of compounds with differing properties, two of the most commonly used EDs are SDB-RPS and SDB-XC. Our previous study [24] showed a similar performance of these two solid-phase sorbents for semi-polar and polar compounds, but our preliminary experiments showed slightly better and more repeatable recoveries for SDB-XC (data not shown When considering the overall mean recoveries, more than half of the compounds had a recovery above 80%. Three had a recovery above 60% and three (fluopyram, metholachlor and sulfamethoxazole) between 42 and 53% (Table 1).…”
Section: Empore™ Disk Performance and Recoveriesmentioning
confidence: 60%
See 2 more Smart Citations
“…Due to their ability to retain a large range of compounds with differing properties, two of the most commonly used EDs are SDB-RPS and SDB-XC. Our previous study [24] showed a similar performance of these two solid-phase sorbents for semi-polar and polar compounds, but our preliminary experiments showed slightly better and more repeatable recoveries for SDB-XC (data not shown When considering the overall mean recoveries, more than half of the compounds had a recovery above 80%. Three had a recovery above 60% and three (fluopyram, metholachlor and sulfamethoxazole) between 42 and 53% (Table 1).…”
Section: Empore™ Disk Performance and Recoveriesmentioning
confidence: 60%
“…Compounds selected for the study were considered to be ecotoxicologically relevant according to the literature [19][20][21][22][23] and were detected in GW in a previous study [24]. Table S1).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 types of pharmaceuticals (acetaminophen, atenolol (ATL), CAF, CBZ, ciprofloxacin, clofibric acid, diclofenac (DCF), hydrochlorothiazide, IBU, ketotifen (KTF), naproxen (NPX), and sulfamethoxazole (SMX)), three types of personal care products (DEET, triclocarban (TCC), and triclosan (TCS)), and five types of ASWs (acesulfame K, cyclamate, saccharine, aspartame, and sucralose) were identified in groundwater (being used as drinking water directly) at the Ganges River Basin (India) (Sharma et al, 2019). 16 pesticides and 14 pharmaceuticals were detected in groundwater in the eastern metropolitan area of Lyon (France), and among which, adenine, adenosine, and nicotinamide were detected for the first time (Pinasseau et al, 2019). Vystavna et al (2019) collected the data on hydrochemical parameters and stable isotopes of groundwater in urban and forest springs over a period of 12 months in the Kharkiv region (Ukraine) and found that the CECs detected in groundwater were various drugs (mainly CAF, nikethamide, riluzole, etc.…”
Section: Drinking Water and Groundwatermentioning
confidence: 99%
“…Compared with polar organic chemical integrative sampler (POCIS), this sampler ANNUAL LITERATURE REVIEW did not have polyethersulfone (PES) diffusion membrane overlying the receiving phase, avoiding some compounds with higher hydrophobicity being trapped in the PES membrane and subsequently reducing the analytical sensitivity (Gao, Xu, Ma, Rao, & Wang, 2019). Pinasseau et al (2019) reported an Empore™ disk-based passive samplers, using SDB-RPS (styrene-divinylbenzene-reversed-phase sulfonate) and SDB-XC (poly(styrene-divinylbenzene)) as adsorbents, which have been considered to be able to trap hydrophobic and semi-polar compounds that might present in studied site. They designed a special deployment rig that comprised of stainless-steel inner mesh cylindrical cage with circular strengthening rods, and a similar size outer stainless-steel mesh to secure the Empore™ disks (passive samplers).…”
Section: Samplermentioning
confidence: 99%